2013
DOI: 10.3109/21678421.2013.785569
|View full text |Cite
|
Sign up to set email alerts
|

Motor and extramotor neurodegeneration in amyotrophic lateral sclerosis: A 3T high angular resolution diffusion imaging (HARDI) study

Abstract: In amyotrophic lateral sclerosis (ALS), diffusion weighted magnetic resonance imaging (DW-MRI) has produced mounting evidence of a widespread white matter (WM) damage within motor and extramotor pathways. To provide novel information about the degenerative process in ALS, overcoming some of the limitations imposed by diffusion tensor imaging (DTI), we performed a high angular resolution diffusion imaging (HARDI) analysis of DW-MRI data. Generalized fractional anisotropy (GFA) was evaluated in 19 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 56 publications
3
34
0
2
Order By: Relevance
“…The most pronounced decreased FA and increased have been shown in the posterior limb of internal capsule [34,35].…”
Section: Dti Imagesmentioning
confidence: 99%
“…The most pronounced decreased FA and increased have been shown in the posterior limb of internal capsule [34,35].…”
Section: Dti Imagesmentioning
confidence: 99%
“…Apart from the study of Grapperon et al who reported an increase in FA (Grapperon, Verschueren et al 2014), all other studies found reduction of the average FA over the entire CST(Abe, Yamada et al 2004, Karlsborg, Rosenbaum et al 2004, Iwata, Aoki et al 2008, Pettit, Bastin et al 2012, Prudlo, Bissbort et al 2012, Agosta, Caso et al 2013, Bastin, Pettit et al 2013, Rajagopalan, Yue et al 2013, Trojsi, Corbo et al 2013, Crespi, Cerami et al 2014, Floeter, Katipally et al 2014 as well as at different levels along the tract , Karlsborg, Rosenbaum et al 2004, Mitsumoto, Ulug et al 2007, Rajagopalan, Yue et al 2013, Hübers, Müller et al 2015. This was more apparent in the right CST (Sarica, Cerasa et al 2014) with RD increase (Zhang, Schuff et al 2009), superiorly (Bede, Bokde et al 2013) caudally (Zhang, Yin et al 2014, Hübers, Müller et al 2015 and rostrally (Filippini, Douaud et al 2010) and with MD increases , Prudlo, Bissbort et al 2012, Floeter, Katipally et al 2014 at the level of the internal capsule (Sach, Winkler et al 2004).…”
Section: Projection Fibersmentioning
confidence: 97%
“…The latter study found that there was a trend towards significant correlation between ALSFRS-R scores and FA (Sarica, Cerasa et al 2014). Other studies found no correlation between FA and ALSFRS-R and disease duration (Furtula, Johnsen et al 2013, Woo, Wang et al 2014 or disease progression (Trojsi, Corbo et al 2013). …”
mentioning
confidence: 94%
See 2 more Smart Citations